Lasing in Ne-Like Argon capillary discharge at low current and the effect of current prepulse - Kwek, K.H.; Tan, C.A. (2008)
The output characteristics of saturated capillary discharge 46.9 nm Ne-Like argon soft x-ray laser obtained with relatively low main discharge current of less than 20 kA, with the lowest being 9 kA. The 3 mm diameter and 200 mm long alumina capillary with Argon filling pressure range between 0.1-0.4 mbar was pumped by a discharge current with a quarter-cycle of about 40 ns. A current pulse with a typical RC shape (decay time ~30 us) was used as a prepulse. Measurements indicate that the laser output is affected by the timing of the application of the prepulse. This effect is most significant when the time delay between the application of the prepulse and the onset of the main current is arount 2 to 4 us, and beyond these times, the effect is less significant.